2022
DOI: 10.3310/aafo2475
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing medicines in older people living with multimorbidity and polypharmacy: the TAILOR evidence synthesis

Abstract: Background Tackling problematic polypharmacy requires tailoring the use of medicines to individual needs and circumstances. This may involve stopping medicines (deprescribing) but patients and clinicians report uncertainty on how best to do this. The TAILOR medication synthesis sought to help understand how best to support deprescribing in older people living with multimorbidity and polypharmacy. Objectives We identified two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 215 publications
0
35
0
3
Order By: Relevance
“…Concurrently, uncertainty and sometimes fear about deprescribing outcomes undermined considerations of the benefit of deprescribing. This bias towards maintaining the status quo resulting in ongoing medication use reflects the results of studies conducted elsewhere (Reeve et al, 2022). For example, GPs in Denmark were more likely to decide to continue medications because of ambiguity about the appropriateness of deprescribing (Nixon & Vendelø, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Concurrently, uncertainty and sometimes fear about deprescribing outcomes undermined considerations of the benefit of deprescribing. This bias towards maintaining the status quo resulting in ongoing medication use reflects the results of studies conducted elsewhere (Reeve et al, 2022). For example, GPs in Denmark were more likely to decide to continue medications because of ambiguity about the appropriateness of deprescribing (Nixon & Vendelø, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…The Tailor report offers some answers. The Tailor evidence synthesis was funded by NIHR to further understand deprescribing for patients with polypharmacy (Reeve et al., 2022). The core aim for Tailor was to challenge the barriers we have described to improvements in the management of polypharmacy and how to tailor medicines to individuals.…”
Section: Tailor and Dextrusmentioning
confidence: 99%
“…13 14 The emphasis that clinicians in the study by Swinglehurst and colleagues placed on continuity is echoed in a recent review of interventional strategies for effective deprescribing in older people with polypharmacy. 15 The review identified continuity and trust as critical mechanisms underpinning effective interventions, but discussed the roles of multiple types of continuity of care, alongside relational continuity, in supporting the effective management of polypharmacy. The review authors argue that informational continuity (access to and use of information about past events and personal circumstances to support personcentred decision-making) and management continuity (consistency in management approach reflecting changing patient needs) can play a role in the context of a more multidisciplinary and team-based approach.…”
Section: Continuity and Polypharmacymentioning
confidence: 99%
“…Second, developing our understanding of what person-centred care means in the context of medicines optimisation and medication reviews. 15 Prescribers should recognise the patient as an expert in their own experiences of medication, and in what they want to achieve from their medication. 17 Person-centred care, though, extends further than just involving the patient.…”
Section: Coordinating Medicines Management Within Multidisciplinary T...mentioning
confidence: 99%
See 1 more Smart Citation